Ventilação mecânica : evidências para o cuidado de enfermagem - Rodrigues, Yarla Cristine Santos Jales (2012)
To assess nurses’ knowledge related to mechanical ventilation in intensive care units (ICUs) of a referral hospital in Fortaleza. This is a Cross-sectional and quantitative study. Sample was made by nurses in ICUs on a total of 43 nurses, with a questionnaire. Data collection was conducted between February and March 2011. The analysis, data were transcribed and tabulated in Excel program, organized in tables, interpreted and justified based on the literature pertinent. Majority female (88.4%), time in the ICU prevailed from zero to five years (48.8%), most of the nurses are not experts in the ICU (79.0%). The evaluation of the cycling of the mechanic ventilation at volume was not satisfactory, 65.1%. It was noted that the participation of nurses is minimal in defining parameters, in participation of extubation, weaning and aspiration. It was concluded that nurses must expand their knowledge and implement nursing care to patients in mechanical ventilation. The training programs on mechanic ventilation for nurses should be encouraged by working institutions in order to qualify the nursing care to patients in need of ventilatory support.